Brief sounds evoke prolonged responses in anesthetized ferret auditory cortex. - Campbell, R; Schulz, A; King, A; Schnupp, J (2010)
Neurons in the auditory cortex of anesthetized animals are generally considered to generate phasic responses to simple stimuli such as tones or noise bursts. In this paper, we show that under ketamine/medetomidine anesthesia, neurons in ferret auditory cortex usually exhibit complex sustained responses. We presented 100-ms broad-band noise bursts at a range of interaural level differences (ILDs) and average binaural levels (ABLs), and used extracellular electrodes to monitor evoked activity over 700 ms poststimulus onset. We estimated the degree of randomness (noise) in the response functions of individual neurons over poststimulus time; we found that neural activity was significantly modulated by sound for up to approximately 500 ms following stimulus offset. Pooling data from all neurons, we found that spiking activity carries significant information about stimulus identity over this same time period. However, information about ILD decayed much more quickly over time compared with information about ABL. In addition, ILD and ABL are coded independently by the neural population even though this is not the case at individual neurons. Though most neurons responded more strongly to ILDs corresponding to the opposite side of space, as a population, they were equally informative about both contra- and ipsilateral stimuli.